A five-decade analysis of work-life balance among women through systematic literature review and bibliometric analysis - Mubashir Majid Baba; Chitra Krishnan; Neelni Giri Goswami (Future Business Journal)
Abstract Over the past five decades, the concept of work-life balance has undergone a significant transformation, particularly in the context of women who continue to navigate the complex interplay between professional responsibilities and personal commitments. This study offers a comprehensive overview of the research landscape on women’s work-life balance by integrating a systematic literature review with a bibliometric analysis. It aims to identify the prevailing themes and sub-themes that have shaped the discourse over time, while also highlighting the notable trends and shifts that characterize current research in the field. By analyzing the intellectual structure, publication patterns, and scholarly contributions, this study provides valuable insights into how the field has evolved and where future research might be directed. The findings not only deepen the understanding of the challenges women face in achieving work-life balance but also suggest potential areas for the development of more robust and targeted models and policy interventions to address these enduring issues.